Analisis Survival Kecepatan Kekambuhan Stroke - Karina Pramudita; Hari Basuki Notobroto (Universitas Airlangga, 2017)
The objective of this study was to apply cox regression to factor analysis of stroke recurrence rate. This type of research was applied research on secondary data. The samples were 178 first stroke patients who are enrolled in inpatient period January to December 2011 and then made observations on the incidence of recurrent strokes up in February 2017 in medical record. Analysis techniques using Cox regression analysis on risk factors of stroke recurrence rate in RSAU dr. Esnawan Antariksa Halim Perdana Kusumah Jakarta. The analysis exhibited that the rate of recurrence of stroke has the same risk between categories of obesity. Stroke patients with a history of hypertension had a risk of a stroke recurrence rate of 5.594 times more likely than stroke patients with no history of hypertension, stroke patients with a history of diabetes mellitus had a risk of stroke recurrence rate of 1.912 times more likely than stroke patients with no history of diabetes mellitus, stroke patients with a history of dyslipidemia The risk of a recurrence rate of stroke was 2.153 times more likely than stroke patients without a history of dyslipidemia, and stroke patients with a history of heart abnormalities had a risk of recurrent stroke rates of 2.321 times more likely than stroke patients without a history of heart abnormalities. For stroke patients with a history of hypertension, diabetes mellitus, dyslipidemia and a history of cardiac abnormalities, need to do regular check-ups and controls every month to avoid recurrence of stroke.